The role of remote ischemic preconditioning in the treatment of atherosclerotic diseases. Issue 6 (30th August 2013) - Vasdekis, Spyros N.; Athanasiadis, Dimitrios; Lazaris, Andreas; Martikos, Georgios; Katsanos, Aristeidis H.; Tsivgoulis, Georgios; Machairas, Anastasios; Liakakos, Theodoros
Abstract Background Remote ischemic preconditioning (RIPC) is the application of a transient and brief ischemic stimulus to a distant site from the organ or tissue that is afterward exposed to injury ischemia, and has been found to reduce ischemia–reperfusion injury (IRI) in various animal models. RIPC appears to offer two distinct phases of endothelial IRI protection, which are presumably mediated through neuronal and humoral pathways. Methods We conducted a comprehensive literature review on the available published data about the potential effect of RIPC in patients undergoing IRI in one or more vital organs. Results Our search highlighted 24 randomized clinical trials about the effect of RIPC on variable clinical settings (abdominal aortic aneurysm repair, open heart surgery, percutaneous coronary intervention, living donor renal transplantation, coronary angiography, elective decompression surgery, carotid endarterectomy, recent stroke, or transient ischemic attack combined with intracranial carotid artery stenosis). Most of the trials focused on postoperative cardiac or renal function after RIPC with conflicting results. Preconditioning protocols, age limits, comorbidities, and concomitant drug use varied significantly across trials, and therefore no firm conclusions can be drawn using the available data. However, no severe local adverse events were observed in any patient undergoing limb or arm preconditioning. Conclusions RIPC is a safe and well‐tolerated procedure that may constitute a potentially promising innovative treatment in atherosclerotic diseases. Large, multicenter, randomized clinical trials are required to determine an optimal protocol for the RIPC procedure, and to evaluate further the potential benefits of RIPC in human ischemic injury.